Cardiac deficiency of P21-activated kinase 1 promotes atrial arrhythmogenesis in mice following adrenergic challenge - Jung, E; Capel, R; Jiang, C; Venturi, E; Neagu, G; Pearcey, S; Zhou, Y; Zhang, Y; Lei, M (The Royal Society, 2023)
P21-activated kinase 1 (Pak1) signalling plays a vital and overall protective role in the heart. However, the phenotypes of Pak1 deficiency in the cardiac atria have not been well explored. In this study, Pak1 cardiac-conditional knock-out (cKO) mice were studied under baseline and adrenergic challenge conditions. Pak1cKO mice show atrial arrhythmias including atrial fibrillation (AF) in vivo, detected during anaesthetized electrocardiography without evidence of interstitial fibrosis upon Masson's trichrome staining. Optical mapping of left atrial preparations from Pak1 cKO mice revealed a higher incidence of Ca2+ and action potential alternans under isoprenaline challenge and differences in baseline action potential and calcium transient characteristics. Type-2 ryanodine receptor (RyR2) channels from Pak1 cKO hearts had a higher open probability than those from wild-type. Reverse transcription-quantitative polymerase chain reaction and Western blotting indicated that pCamkIIδ and RyR2 are highly phosphorylated at baseline in the atria of Pak1 cKO mice, while the expression of Slc8a2 and Slc8a3 as a Na+–Ca2+ exchanger, controlling the influx of Ca2+ from outside of the cell and efflux of Na+ from the cytoplasm, are augmented. Chromatin immunoprecipitation study showed that pCreb1 interacts with Slc8a2 and Slc8a3. Our study thus demonstrates that deficiency of Pak1 promotes atrial arrhythmogenesis under adrenergic stress, probably through post-translational and transcriptional modifications of key molecules that are critical to Ca2+ homeostasis.